IMPLEMENTATION OF MEDICAL AND SOCIAL REHABILITATION FOR ADDICTIVE AND NARCOTICS ABUSE - Ibnu Sakdan; Dahlan Ali; Mahfud (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2019)
This study examines the reasons for judges not ordering rehabilitation for narcotics abuse offenders, as stipulated in Article 127 paragraph (2) of Law No. 35 of 2009 concerning Narcotics. It also investigates the implementation of medical and social rehabilitation conducted in the jurisdictions of Banda Aceh and Aceh Besar. In handling narcotics abuse cases in Banda Aceh and Jantho from 2015 to 2017, there was only one decision ordering rehabilitation for the offenders, while others were sentenced to prison terms. The judge did not order for rehabilitation, because the expert was not present at the court to explain that the narcotics addicts needed rehabilitation, the offenders denied that they were narcotics addicts, and the public prosecutor had never demanded the defendant to be rehabilitated. In 2015 and 2016, the rehabilitation program was implemented by the National Narcotics Agency (BNN), but it stopped in the following year due to the insufficient budget. The rehabilitation carried out is medical and social rehabilitation, an integrated treatment to cure addicts of narcotics addiction as well as mental and social recovery so that ex-addicts are ready to return to society. Abstrak: Artikel ini meneliti mengapa hakim tidak memutuskan rehabilitasi bagi pelaku penyalahgunaan narkotika sebagai mana ketentuan Pasal 127 ayat (2) Undang-undang No. 35 tahun 2009 tentang Narkotika, serta meneliti bagaimana pelaksanaan rehabilitasi medis dan sosial yang dilaksanakan di wilayah hukum Banda Aceh dan Aceh Besar. Dalam penanganan perkara penyalah guna narkotika di Pengadilan Negeri Banda Aceh dan Pegadilan Negeri Jantho dalam tahun 2015 sampai dengan tahun 2017 hanya ada satu putusan yang memerintahkan merehabilitasi pelaku, sedangkan pelaku lain dihukum hukuman penjara. Hakim tidak memutuskan rehabilitasi, karena tidak dihadirkannya ahli ke persidangan untuk menerangkan bahwa pecandu narkotika memerlukan rehabilitasi, dan pelaku tidak mau mengakui sebagai pecandu narkotika, serta penuntut umum juga tidak pernah menuntut terdakwa untuk direhabilitasi. Pada tahun 2015 dan 2016 program rehabilitasi dilaksanakan oleh pihak BNN, namun tahun berikutnya tidak dilaksanakan lagi karena tidak tersedianya anggaran. Rehabilitasi yang dilaksanakan adalah rehabilitasi medis dan sosial berupa pengobatan secara terpadu untuk membebaskan pecandu dari ketergantungan narkotika serta pemulihan mental maupun sosial sehingga bekas pecandu siap kembali dalam masyarakat. Kata Kunci: Narkotika, Rehabilitasi, Kebijakan